A checklist of the dragonflies from the North-Western of Isiboro-Sécure Indian Country and National Park, Bolivia - Pessacq, Pablo (2015)
Fil: Pessacq, Pablo. Centro de Investigaciones Esquel de Montaña y Estepa Patagónicas; Argentina